EFFECT OF THE PHYSICAL ACTIVITY OF PRESCHOOL CHILDREN ON THE STRENGTH ENDURANCE OF ABDOMINAL, TRUNK AND GLUTEAL MUSCLES - V. Pavlova; R. Paskaleva; V. Ivanova (Trakia Journal of Sciences)
PURPOSE. The objective of this study is to investigate the static strength endurance of abdominal, trunk and gluteal muscles both in physically active and physically inactive overweight children. MATERIAL AND METHODS. The object of study are 104 children aged 5-6 years in the period 2017-2018 on the territory of the town of Stara Zagora. To investigate the motor activity of children the survey method was used. To determine efficiency of trunk, abdominal and gluteal muscles modified Kraus-Weber test was used according to V. Zhelev, L. Venova. RESULTS. Weaker abdominal and trunk muscles were found in physically inactive children with no statistically significant differences (Р>0.05) between physically active and physically inactive ones. However, the results show the presence of statistically significant differences (P=0.01) of the mean values for the static strength endurance of gluteal muscles in physically active children 13,9±8,6 sec. and physically inactive children 10,3±9,4 sec. with the latter having weaker gluteal muscles, respectively. CONCLUSIONS. Further studies are needed to establish the relationship between the increased body mass of children and the strength endurance of abdominal, trunk and gluteal muscles of physically active and physically inactive children as an indicator counteracting total muscle hypotonia.